2020
DOI: 10.1186/s12911-020-01236-5
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency and effectiveness of surgery information systems in Iran

Abstract: Background Despite the prevalent use and advantages of information systems in hospitals, some have failed to meet their predefined objectives. Surgery information system (SIS) is a sub-system of a hospital information system. Its effective and efficient operation could enhance patient care in the busy environment of operating rooms with multiple tasks. The objective of this study was to evaluate the effectiveness and efficiency of SIS in three educational hospitals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In our study, the efficiency and effectiveness of the SSO electronic prescribing system had no significant relationship with gender, age, work experience, specialization, and computer skills. Likewise, previous studies (3033) showed that there was no relationship between age, gender, and working experience with computers of users with some electronic systems such as nursing information systems (NIS), electronic medical record system, and surgery information system. Contrary to the above results, in the two studies on the NIS and computerized physician order entry (34;35), the age of users impacted their satisfaction levels, and it was found that older users were more satisfied than their younger counterparts.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, the efficiency and effectiveness of the SSO electronic prescribing system had no significant relationship with gender, age, work experience, specialization, and computer skills. Likewise, previous studies (3033) showed that there was no relationship between age, gender, and working experience with computers of users with some electronic systems such as nursing information systems (NIS), electronic medical record system, and surgery information system. Contrary to the above results, in the two studies on the NIS and computerized physician order entry (34;35), the age of users impacted their satisfaction levels, and it was found that older users were more satisfied than their younger counterparts.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are in line with the results of a study concerning the correlation between satisfaction, effectiveness, and efficiency (36). Also, the results of two studies (16;33) showed that there is a significant correlation between the efficiency and effectiveness of the surgery information system and that of the diabetes mHealth system.…”
Section: Discussionmentioning
confidence: 99%
“…As a rule of thumb, effectiveness can be achieved when users perform their activities and tasks wholly and accurately via the system [ 59 ]. In a complex healthcare environment, the effectiveness of health information systems reduces errors by improving legibility, completeness and accuracy of information required for users to make decisions and perform their tasks, having a positive effect on improving quality of care [ 60 62 ]. It can be stated that, according to the results of the present study and Khajouei et al's study [ 28 ], the HE method is a validated method to identify satisfaction problems.…”
Section: Discussionmentioning
confidence: 99%
“…Within the dynamic healthcare environment, healthcare information systems are being constantly implemented, changed and updated [ 65 67 ]. Meanwhile, usability problems and users’ unfamiliarity with the user interface lead users to spend more time completing tasks by the system, hence, decreasing the efficiency [ 59 , 62 ]. On the other hand, training time in HISs is highly limited for the healthcare workers such as nurses who are essentially required to learn how to work with the system while doing their duties [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Carrying out nursing information technology education in colleges and universities has become popular [26]. HISs not only reduce cost and time but also reduce medical errors and patient mortality, promote nursing workfow, and improve the quality of nursing services for patients [27,28]. Although the clinical application of HISs still faces many obstacles, including imperfect systems, data loss, information security problems, and a lack of systematic training [29,30], such systems play an important role in clinical practice.…”
Section: Nursing Students Generally Support the Use Of Nursing Simula...mentioning
confidence: 99%